A NOTE ON GENSYS’ MINIMALITY - SACCAL, Alessandro (Theoretical and Practical Research in Economic Fields; Vol 12 No 1 (2021): TPREF, Volume XII, Issue 1(23), Summer 2021DO - 10.14505/tpref.v12.1(23).08, 2021)
Gensys’ non-minimality is shown analytically and necessary and sufficient conditions for vector autoregression representations of states in outputs are presented.